A meta-analysis of the association between Growth Hormone (GH) gene polymorphism and growth traits in cattle breeds - Bayraktar, M; Özdemir, M (Journal of the Hellenic Veterinary Medical Society, 2022)
GH gene is one of the important genes that affect the productive and physiological traits in livestock. This study aimed to use a meta-analysis to determine the association of the GH gene with growth traits in cattle. Four different genetic models were used: dominant LL + LV versus VV, recessive LL versus LV + VV, complete over dominant LL+VV vs. LV and co-dominant LL vs. LV, LL vs. VV and LV vs. VV. The random-effect model was used in data analysis based on I2. Meta-analysis showed an effect of GH genotypes on the birth weight (BW) under the recessive (p<0.05) and complete over dominant (p<0.01) models. However, no association (p>0.05) was found under the dominant model. In terms of co-dominant model, the GH polymorphism showed a significant association with BW (SMD = 0.359, 95% CI = 0.119 to 0.599, p = 0.003) under LL vs. LV genotype combination patterns. No association was found between GH polymorphism and BW under LL vs. VV genotype combination. The results showed that the LL genotype had a significant effect on BW traits from LV and VV genotypes when comparing the models. The results showed an effect of the GH on ADG under four genetic models (p<0.05).